The Determinants of Team Success in the NHL an Examination: Pre and Post-Lockout - Marella, David perry (Université d'Ottawa | University of Ottawa, 2010)
In this paper I examine the determinants of team success in the National Hockey League (NHL), and whether they changed with the introduction of the new Collective Bargaining Agreement (CBA) in 2005. Team success is defined in two ways: first, whether a te